Estimating the cost of COVID-19 vaccine deployment and introduction in Ghana using the CVIC tool. Issue 12 (15th March 2022) - Nonvignon, Justice; Owusu, Richmond; Asare, Brian; Adjagba, Alex; Aun, Yap Wei; Yeung, Karene Hoi Ting; Azeez, Joycelyn Naa Korkoi; Gyansa-Lutterodt, Martha; Gulbi, Godwin; Amponsa-Achiano, Kwame; Dadzie, Frederick; Armah, George E.; et al.
Highlights: Current COVID-19 vaccine supply market means LMICs will have to rely on a combination of different sources/types of vaccines to meet their demand. Deployment of COVID-19 vaccine plans in Ghana will cost $348.7–$436.1 million for coverage of 17.5 million of eligible Ghanaians. Vaccine cost constitute 78–83% of total cost whereas the total vaccination cost is 0.48–0.60% of the country's 2020 GDP. The WHO-UNICEF CVIC tool is useful for comprehensive COVID-19 vaccine deployment costing and resource planning. Abstract: Background: This study estimated cost of COVID-19 vaccine introduction and deployment in Ghana. Methods: Using the WHO-UNICEF COVID-19 Vaccine Introduction and deployment Costing (CVIC) tool Ghana's Ministry of Health Technical Working Group for Health Technology Assessment (TWG-HTA) in collaboration with School of Public Health, University of Ghana, organized an initial two-day workshop that brought together partners to deliberate and agree on input parameters to populate the CVIC tool. A further 2–3 days validation with the Expanded Program of Immunization (EPI) and other partners to finalize the analysis was done. Three scenarios, with different combinations of vaccine products and delivery modalities, as well as time period were analyzed. The scenarios included AstraZeneca (40%), Johnson & Johnson (J&J) (30%), Moderna, Pfizer, and Sputnik V at 10% each; with primary schedule completed by second half of 2021 (Scenario 1); AstraZeneca (30%), J&J (40%), Moderna, Pfizer, and Sputnik V at 10% each with primary schedule completed by first half of 2022 (Scenario 2); and equal distribution (20%) among AstraZeneca, J&J, Moderna, Pfizer, and Sputnik V with primary schedule completed by second half of 2022 (Scenario 3). Results: The estimated total cost of COVID-19 vaccination ranges between $348.7 and $436.1 million for the target population of 17.5 million. These translate into per person completed primary schedule cost of $20.9–$26.2 and per dose (including vaccine cost) of $10.5–$13.1. Again, per person completed primary schedule excluding vaccine cost was $4.5 and $4.6, thus per dose excluding vaccine also ranged from $2.2 – $2.3. The main cost driver was vaccine doses, including shipping, which accounts for between 78% and 83% of total cost. Further, an estimated 8, 437–10, 247 vaccinators (non-FTEs) would be required during 2021–2022 to vaccinate using a mix of delivery strategies, accounting for 8–10% of total cost. Conclusion: These findings provide the estimates to inform resource mobilization efforts by government and other partners.